Corrigendum to “Inverse scattering problem with Levinson formula for eigenparameter‐dependent discrete Sturm‐Liouville equation” - Koprubasi, Turhan; Mohapatra, R. N. (Wiley, 2023)
There are three oversights in the zeros of the Jost function in Lemma 3.3 (page 1469), in the Delta function in Lemma 3.4 (page 1471), and in the continuity of the scattering function at zero in Theorem 4.2 (page 1473). Therefore, we have corrected Lemma 3.3, Lemma 3.4, and Theorem 3.5 with their proofs and Section 4.